IMPLEMENTASI HAK PELAYANAN KESEHATAN PASIEN TIDAK MAMPU UNTUK MEWUJUDKAN PERLINDUNGAN HUKUM DI RS MARDI RAHAYU KUDUS - Yoci Santoso, Kristian; Wibawa, Iskandar (IBLAM LAW REVIEW, 2024)
This research was carried out with the aim of finding out the implementation of health care rights for indigent patients to realize legal protection at Mardi Rahayu Kudus Hospital. This research used a clinical approach. The results of the research explain that the right that patients have is to obtain complete and complete health services. Likewise, poor patients should receive services that meet the requirements of scientific competence. Health services available at hospitals are emergency rooms, specialist clinics, laboratories, inpatient centers, morgues and many more. Regarding the approach to the community, especially for people who do not have the means to obtain inpatient services in hospitals, namely through emergency departments or professional clinics, and if patients use health coverage or insurance, they can be presented in 2 examples. Apart from that, people with disabilities must also meet the requirements set by the Government. The means of prison protection for indigent sufferers that can be provided by hospitals is to provide superior, complete and comprehensive health services in accordance with scientific competency standards.